Evaluation of Cerebrospinal fluid adenosine deaminase activity as a complimentary tool in the early diagnosis of tuberculous meningitis in children - Pan, A; Biswas, A; Chaterjee, A; Kumar, R (Journal of College of Medical Sciences-Nepal, 2012)
The diagnosis of tuberculous meningitis cannot be made or excluded on the basis of clinical findings. Definite laboratory diagnosis is cumbersome and time consuming. Delay in diagnosis and institution of proper treatment is directly related to poor outcome and sequalae. Adenosine deaminase activity (ADA) was estimated in cerebrospinal fluid (CSF) in addition to routine CSF analysis of 32 patients of tuberculous meningitis (TBM) and 7 patients of partially treated pyomeningitis (PTM), 10 patients aseptic meningitis (AM) and 13 patients pyogenic meningitis (PM). Mean ADA levels in CSF of TBM patients were higher (15.42 U/L) as compared to 7.21 U/L, 6.41 U/L and 7.50 U/L in PTM, AM and PM respectively. This difference of ADA values in CSF between TBM and other types of meningitis was statistically significant (p<0.01). ADA values were also compared with other biochemical and cytological parameters of CSF & a positive correlation was found with CSF protein level. Sensitivity and specificity of ADA levels in CSF of children to diagnose tuberculous meningitis was 75% and 90% respectively at 10 U/L cut off of ADA levels in CSF. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 17-23 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6833